LONG-TERM INDONESIAâS NICKEL SUPPLY CHAIN STRATEGY FOR LITHIUM-ION BATTERY AS AN ENERGY STORAGE SYSTEM - Fadilah Akbar, Figo
The world energy demand is as high as ever, carbon-based energy such as oil, gas, and coal are the primary energy supply used to cope with the demand. The threat of climate change became more evident as the world population from across the world began to feel the impact. The rapid rate of sustainable energy sources such as solar and wind needs an energy storage system, as such sources of its energy are not always available. One of many kinds of energy storage systems is lithium-ion batteries. The demand for lithium-ion batteries reflects the world's demand for sustainable energy, making material for Lithium-ion batteries the new oil. Nickel in Lithium-ion batteries is one of significant materials used to make this battery. Indonesia has been one of the world’s top producers of nickel and has the most reserve in the world. Most Indonesian nickel has been exported as raw ore to be processed in other countries. Recognizing its potential, the government has been imposing a law banning the export of raw nickel ore. The government constructs smelters to purify the ore to get a higher nickel content. But still, Indonesia has issues to work on so its plan will proceed as intended. Issues such as extensive political involvement, complicated government bureaucracy, and inconsistent policies and laws. The big investment in mining infrastructure must align with the investment in the people who will manage it and who are going to execute the actual plan.